Base de Datos Urbano – Arquitectónica: herramienta para la comprensión histórica y la interpretación estilística de Maracaibo. - Rodríguez O., Laura (Universidad del Rosario, 2010)
In the Venezuela cities, and particularly in Maracaibo, the dynamics has caused the deterioration, transformation, or desappearence of architectural works of cultural interest. In order to rescue the urban and architectural image that has characterized the city of Maracaibo in the last 50 years, a case-study approach was used in the analysis of the main artery called Avenida las Delicias.